Re-examination of son-preference based on attitude structure theory under the background of gender imbalance in China - Shang, Zijuan; Chi, Baihui; Liu, Ze (Frontiers in Psychology, 2023)
The gender imbalance in China has a long history, and the consequences have begun to emerge, threatening the healthy operation of the population system, and seriously affecting the New Journey of Socialist Construction with Chinese Characteristics in the New Era. Faced with a persistently high sex ratio at birth, the paper introduces the theory of attitude structure to construct an analytical framework for the influence factors of son preference, re-examines the culture of son preference in the context of gender imbalance, and selects the micro-personal data from Jiangxi, Guangxi, Guizhou and Shaanxi Province for empirical research. The results show that the inheritance of the surnames, the utility of elderly care and the social value in the son's utility evaluation are the main influencing factors in the formation of the son preference; social gender assessment, perception of gender imbalance, personal income, education level, health status and the number of existing children all have different effects on son preference. After comparing the two factors of son's utility evaluation and gender imbalance perception, it is discovered that after China enters a gender imbalanced society, the perception of gender imbalance effectively reduces the preference for boys, and the son preference is the result of rational choice in people's fertility process. Based on the above research, the paper proposes policy recommendations on both macro and micro levels from the viewpoint of public governance.